2016
DOI: 10.1007/s10346-016-0739-x
|View full text |Cite
|
Sign up to set email alerts
|

Do landslides follow landslides? Insights in path dependency from a multi-temporal landslide inventory

Abstract: Landslides are a major category of natural disasters, causing loss of lives, livelihoods and property. The critical roles played by triggering (such as extreme rainfall and earthquakes), and intrinsic factors (such as slope steepness, soil properties and lithology) have previously successfully been recognized and quantified using a variety of qualitative, quantitative and hybrid methods in a wide range of study sites. However, available data typically do not allow to investigate the effect that earlier landsli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
109
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 51 publications
12
109
1
3
Order By: Relevance
“…The following are some of the physical factors that authors have noted that affect the shape of landslides (including source area, deposition and runout): landslide type (Dikau, ), topography (Guthrie and Evans, ), history of landsliding (McCalpin, ), history of landsliding in the immediate vicinity (Samia et al ., ), and wet or dry triggering mechanisms (Legros, ; Yang and Lee, ). In addition, soil characteristics have been noted to affect the shape of landslide source areas (Klar et al ., ; Lehman and Or, ; Milledge et al ., ) and combined source area and runout (Cardinali et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following are some of the physical factors that authors have noted that affect the shape of landslides (including source area, deposition and runout): landslide type (Dikau, ), topography (Guthrie and Evans, ), history of landsliding (McCalpin, ), history of landsliding in the immediate vicinity (Samia et al ., ), and wet or dry triggering mechanisms (Legros, ; Yang and Lee, ). In addition, soil characteristics have been noted to affect the shape of landslide source areas (Klar et al ., ; Lehman and Or, ; Milledge et al ., ) and combined source area and runout (Cardinali et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Within the landslide literature, there is a relatively small body of work quantitatively investigating landslide shape, which we break up into the following three broad categories typified by five exemplar studies: (i) perimeter-area indices (Pourghasemi et al, 2014); (ii) shape similarity to a circle measure (Samia et al, 2016); and (iii) scaling relationships between landslide dimensions and area (Hovius et al, 1997;Guthrie et al, 2008;Milledge et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Brain et al (2017) proposed that low magnitude earthquakes drive the consolidation and stabilisation of hillslope materials, during periods intervening large earthquakes, while Parker et al (2015) suggested that accrued brittle damage can leave unfailed hillslopes at greater susceptibility to failure following large earthquakes. Samia et al (2017) have suggested that the occurrence of landslides destabilises hillslopes more widely, resulting in greater susceptibility for follow-up landslides over a period of about 10 years. The events included here and in the growing global dataset span a range of likely 5 conditions resulting from these spatial-temporal effects.…”
Section: Further Investigating Sources Of Unconstrained Variabilitymentioning
confidence: 99%
“…In addition, Hergarten (2002) note that the scaling exponent for event sizes obtained by the SOC model is one, which differs from the values observed for natural systems. Finally, the behavior of landslides to be more likely to occur at location of previous landslides, as documented by Samia et al (2017), is not a behavior replicated by SOC models.…”
Section: Earth and Space Sciencementioning
confidence: 95%
“…Another factor that can cause rolloff is lack of temporal resolution when sampling. Samia et al () found that landslides preferentially occur at sites of previous landslides. Thus, a mapping effort on any given date may document a landslide scar that was the site of numerous landslides.…”
Section: Rolloff Observed At Small Event Sizesmentioning
confidence: 99%